Layanan Supervisi, Kepemimpinan Kepala Sekolah, dan Kompetensi Guru Madrasah Aliyah di Kota Kendari - Herlina Herlina (Journal of Islamic Education Policy, 2017)
ABSTRACT This study aims to assess and analyze (1) the level of academic supervision services perceived by the teachers, (2) the effectiveness level of principal leadership perceived by the teachers, (3) performance of the teachers, (4) the significant correlation between academic supervision services and the performance of the teachers, and (5) the significant correlation between the principal’s leadership and the performance of the teachers of Madrasah Aliyah in Kendari City. The population of this research are all teachers of the Madrasah Aliyah in Kendari City which amount to 204 teachers who are government employyees. The sample of the research is determined by using the formula of minimum sampling. From the calculation with the minimum sampling formula known to the population of 204 teachers, a minimum sample size of 64 teachers is obtained. The data on each research variable is collected by using Likert scale questionnaires. The data analysis is conducted using the Z test, correlation, and regression. The results of this research show that (1) the supervision of academic services perceived by the teachers of Madrasah Aliyah in Kendari is quite high, (2) the effectiveness of principal leadership perceived by the teachers of Madrasah Aliyah in Kendari is quite high, (3) the competence of the teachers of Madrasah Aliyah in Kendari City is quite high, (4) there is a significant correlation between the service of academic supervision and the competence of the teachers of Madrasah Aliyah in Kendari City, (5) there is a significant correlation between the leadership of the principal and the competence of the teachers of Madrasah Aliyah in Kendari City, and (6) there is a significant influence of the academic supervision service and the principal’s leadership on the competence of the teachers of Madrasah Aliyah in Kendari City.Keywords: Academic supervision service, principal leadership, teachers’ competence